Bridging gaps in veterinary care: restructuring a community clinic for cultural inclusion in Phoenix, Arizona - Master, Champayne Danae; Vincent, Marjorie Robin; Twomey, Bridgid Ann; Vazquez, Claudia; Robertson, Jyothi Vinnakota (Frontiers in Veterinary Science, 2025)
This case study examines the Arizona Animal Welfare League's (AAWL) efforts to bridge gaps in veterinary care access for Latino communities in Phoenix, AZ, with strategic guidance from JVR Strategies supported by Maddie's Fund. To better understand the specific needs, barriers, and preferences for pet health services, bilingual community needs assessments were conducted through partnerships with PetSmart Charities, Community Alliance Consulting, LLC, the Alliance for Companion Animals Coalition, and the Institute for Human-Animal Connection (IHAC). Insights gained from these needs assessments shaped the restructuring of AAWL's public clinic, leading to the development of a Saturday-only clinic model, bilingual services, outreach, and off-site clinics in targeted zip codes. While the transition posed operational challenges, early results demonstrated increased patient volume, expanded access to care, and created stronger connections with the community. This restructuring created space to listen more deeply to residents through informal conversations and relationship-building in the neighborhoods AAWL sought to serve. Community members consistently pointed to promotoras—local community health workers—as the trusted individuals they already turn to for information, resources, and guidance. Recognizing this, AAWL began building relationships with promotoras, who served as trusted connectors linking community members to AAWL and the veterinary services available to them. This case study examines the organization's process from the initial assessments in 2022 through the clinic's transition to a new model in March 2024, with ongoing adjustments to the model based on community feedback through July 2024. It offers insights into the importance of inclusive needs assessments, community partnerships, and culturally relevant service delivery. These findings provide a framework for organizations aiming to develop community-based veterinary care programs that are both equitable and sustainable.